2019
DOI: 10.1136/bmjopen-2018-023518
|View full text |Cite
|
Sign up to set email alerts
|

PROFIT, a PROspective, randomised placebo controlled feasibility trial of Faecal mIcrobiota Transplantation in cirrhosis: study protocol for a single-blinded trial

Abstract: IntroductionPatients with advanced cirrhosis have enteric bacterial dysbiosis and translocation of bacteria and their products across the gut epithelial barrier. This culminates in systemic inflammation and endotoxaemia, inducing innate immune dysfunction which predisposes to infection, and development of complications such as bleeding, sepsis and hepatic encephalopathy. This feasibility study aims to assess the safety of administering faecal microbiota transplantion to patients with cirrhosis and explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
(16 reference statements)
0
26
0
Order By: Relevance
“…38 Our group has recently completed a safety and feasibility study of FMT in advanced but stable cirrhosis (MELD score 10-16). 39 This study showed that FMT was safe and feasible in this patient group, with a reduction in plasma ammonia levels in FMT treated patients persisting for up to 30 days after treatment. Ammonia is a microbial metabolite and has a central role in the pathogenesis of HE, suggesting a potential role for the use of FMT in the management of this debilitating condition.…”
Section: Manipulating the Gut Microbiota And Gut-liver Axis In Cirrhosismentioning
confidence: 54%
“…38 Our group has recently completed a safety and feasibility study of FMT in advanced but stable cirrhosis (MELD score 10-16). 39 This study showed that FMT was safe and feasible in this patient group, with a reduction in plasma ammonia levels in FMT treated patients persisting for up to 30 days after treatment. Ammonia is a microbial metabolite and has a central role in the pathogenesis of HE, suggesting a potential role for the use of FMT in the management of this debilitating condition.…”
Section: Manipulating the Gut Microbiota And Gut-liver Axis In Cirrhosismentioning
confidence: 54%
“…Woodhouse et al have observed in a PROFIT clinical trial the benefits of fecal microbiota transplantation in the small bowel of cirrhotic patients (Woodhouse et al, 2019 ). Meiglani et al ( 2020 ) also observed that cirrhotic patients with antibiotic-resistant Clostridioides difficile infection (CDI) responded well after FMT treatment.…”
Section: Role Of Fecal Microbial Transplantation (Fmt) In Viral Hepatmentioning
confidence: 99%
“…The trial is aiming to assess not only the safety and tolerability of administering FMT to patients with cirrhosis, but also to try and quantify the effects through measuring changes to the recipient stool microbiome, plasma endotoxin and bacterial DNA levels as well as inflammatory cytokines. 128 …”
Section: Mechanisms Of Damage To Gut Barrier In Arldmentioning
confidence: 99%